2020
DOI: 10.2196/18514
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behaviors of Transition-Aged Youth for Mental Health Concerns: Qualitative Study

Abstract: Background Transition-aged youth are particularly vulnerable to mental health problems, yet they are one of the least likely demographic groups to seek help. Objective The aim of this study is to explore the influences on and patterns in help-seeking for mental health concerns among transition-aged youth who attend postsecondary schools in Canada. Methods A qualitative research design was used, involving 12 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…They are often reluctant to seek professional help because of their sense of shame and tendency toward self-reliance [ 8 ]. The method of getting help based on a network provides a way to overcome these obstacles [ 43 - 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are often reluctant to seek professional help because of their sense of shame and tendency toward self-reliance [ 8 ]. The method of getting help based on a network provides a way to overcome these obstacles [ 43 - 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of accessibility to services and information was also a frequent barrier. According to Stunden et al [ 7 ], the financial pressure associated with traditional care services (e.g., psychiatrists, counselors, and psychotherapists) was often mentioned as an obstacle to treatment seeking and obtaining optimal mental wellbeing. However, Ijadi-Maghsoodi in his research on unsupportive parents, acknowledged that those who had extremely strict parents hesitated to reach out to them for help [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding facilitators, the most reported one was increasing societal and family awareness. This could be linked to Vidourek and Burbage’s [ 7 ] study, which revealed that individuals consistently listed awareness as a component of education, leading to improved mental health and a reduction in stigma [ 7 ]. Sources of external support were also a category that was mentioned in other studies, some of which belonged to Hassett, Dong, and Stunden, who stressed upon the fact that in any situation, individuals such as friends, parents, teachers, job supervisors, counselors, coaches, and semi-formal relationships recognized one’s need for assistance [ 7 , 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, symptoms of anxiety and depression can also act as a barrier to adolescents to receive mental health help; this help-negation effect, those with increased distress having less intent to seek help, has been reported among adolescents with clinical mental disorder and sub-clinical mental distress (D. Clark & Fawcett, 1992;Wilson et al, 2007). Concerningly, receiving informal help from family and friends may also be subject to the help-negation effect (Wilson & Deane, 2010) leading researchers to consider other options that may involve fewer barriers, such as digital selfhelp alternatives (Olesen et al, 2010;Rickwood et al, 2015;Stunden et al, 2020).…”
Section: Individual Barriersmentioning
confidence: 99%